Analysis of the factors determining the development of postoperative pain in patients after knee and hip replacement surgery - K. A. Glemba; A. E. Karateev; M. A. Makarov; S. A. Makarov; E. I. Bialik; S. I. Glukhova; A. M. Lila (Современная ревматология)
Chronic postoperative pain (POP) is a serious complication of total replacement (TR) of the knee (KJ) and hip (HJ) joints.Objective: to determine the factors associated with POP in patients after TR of KJ or HJ.Patients and methods. The study group consisted of 124 patients with knee osteoarthritis or hip osteoarthritis (age 63.6±9.9 years, 63% women and 37% men) who underwent TR of KJ or HJ. POP was defined as pain ≥40 mm on a numerical rating scale persistent for ≥3 months. Its presence was assessed after 3 and 6 months by telephone survey. Comparison of patients with POP and without it was carried out for a number of factors identified before surgery.Results and discussion. The incidence of POP was 27.4%. There was no difference in the incidence of POP in patients after TR of KJ or HJ: 28.1% and 26.9% (p=0.88). POP was statistically significantly associated with parameters such as higher body mass index (BMI); the intensity of pain at rest; general assessment of impairment; WOMAC index pain, stiffness and overall; severity of symptoms of neuropathic pain (PainDETECT); signs of depression and anxiety (HADS).The risk of POP was significantly higher (p<0.05) with BMI >30 kg/m2 (odds ratio, OR 2.755; 95% confidence interval, CI 1.053–7.206), rest pain ≥40 mm on a visual analog scale (OR 1.349; 95% CI 0.478–3.803), PainDETECT scores ≥13 (OR 3.598; 95% CI 1.048–12.36) and HADS depression ≥8 (OR 2.193; 95% CI 0.745–6.454), presence of ≥2 sources of pain (OR 6.996; 95% CI 2.358–20.756).Conclusion. It was found that the risk of POP after TR of KJ and HJ is higher in patients with overweight, severe preoperative pain, signs of neuropathic pain and depression, as well as in the presence of several sources of pain (except for the affected joint, that was replaced surgically).